2DEG characteristics of InAlAs/InP based HEMTs by solving Schrödinger and Poisson equations followed by device characteristics. (10th August 2021) - Lenka, Trupti Ranjan; Singh, Rajan; Tripathy, Susanta Kumar; Goyal, Vishal; Nguyen, Truong Khang; Nguyen, Hieu Pham Trung
Abstract: In this paper the 2DEG characteristics study of InAlAs/InP based high electron mobility transistor (HEMT) structures with two different channel materials (InAlAs and InGaAs) are presented through self‐consistent solutions of Schrodinger and Poisson equations which results in energy bands, sheet charge density, electric field, sheet resistance and CV charactristics. The 2DEG (two dimensional electron gas) is created at the heterointerface of InAlAs/In(Al, Ga)As due to conduction energy band discontinuity. The 2DEG is realised by the presence of subbands at the quantum well. The subbands represent the wave function of electrons. The innovation of this work is that InAlAs and InGaAs with x = 0.75 composition can be best utilised as channel material due to low bandgaps 0.821 and 0.639 eV respectively towards improved 2DEG density, subbands, channel sheet resistance, electric field in the 2DEG and CV characteristics. The DC characteristics comprised of Id Vg, Id Vd, transconductance, cut‐off frequency, maximum frequency of oscillation are extracted through TCAD simulations followed by experimental validation. The InGaAs/InP based HEMT can be a potential candidate for ultra‐high‐speed microwave and millimetre wave applications.